Students' COVID-19 experiences: Integrating knowledge, attitude, and practices strategies for teaching science - Ritchelle Origenes; Blanca A. Alejandro (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The junior and senior high school student experiences regarding their knowledge, attitude, and practices during the COVID-19 pandemic need to explore. This qualitative research uses a phenomenological technique with 20 students (10 JHS and 10 SHS) as a sample. Students learned about the illness through multimedia, filtering misinformation, self-driven data gathering, community support, and teacher-facilitated discussions. They also cultivated their attitude toward the disease through personal experiences and reflection on the pandemic, conducting activities such as experiments to test their acquired knowledge, considering community influences, and due to their self-motivation and appreciation of the right attitude during the pandemic. Finally, they executed practices toward COVID-19 with their parents' and peers' influence and support, collaborative team planning, learning from expert demonstrations, and participating in activity-driven action. JHS and SHS students have had a wide range of experiences during the COVID-19 pandemic regarding knowledge acquisition, inculcation of attitude, and practice implementation toward the disease. The student experiences are eye-openers to science educators. With this, there should be improvements in science education curricula that address the current pandemic and other unforeseen health issues.